Orgram Forest, West Bengal: some Ecological Aspects - Bhattacharya, Archan; Mukherjee, Ambarish (Indian Forester, 2007)
The Orgram forest in Bardhaman District, West Bengal as revealed in the present ecological study, is of Shorea-Acacia-Cassia type. However, it appears to be a mixed type where no single species occupies a very large ecological locus. The species richness value is low and evenness moderate. The probability of getting conspecific individuals on two consecutive efforts is not absolute and the dominance is much higher than the average value for a tropical forest. The community possesses a high biomass value. The relationship between IVI and biomass is positive. The dominance-diversity curve indicates the occupation of top niche by S. robusta and A. nilotica; intermediate niche by S . oleosa and narrow niche spaces by C. fistula and S. cumini. The association index of S. robusta speaks for its accommodative nature to maintain ecological diversity. The CBH classification reveals no seedlings and the absence of regeneration niche in the habitat. The anomalous phytosociological features, which is possibly an outcome of interaction with different stress factors, necessitates proper management.